Organising for continuous innovation: the community of practice approach. (3rd November 2008) - Corso, Mariano; Martini, Antonella; Balocco, Raffaello
This paper aims to develop actionable knowledge to support management in designing and developing a business Community of Practice (CoP) in order to create value for both the organisation and its members. After a two-year field research, with seven case studies performed and three best practices chosen from secondary sources, a six-stage roadmap has been proposed, where both managerial guidelines and actionable models are provided.